Consumers’ Attitude towards Sustainability in Italy: Process of Validation of a Duly Designed Questionnaire - Vittoria Aureli; Alessandra Nardi; Daniele Peluso; Umberto Scognamiglio; Laura Rossi (Foods, 2022)
This study aimed to describe the process of validation of a questionnaire assessing Italian consumers’ perception of food sustainability. The study has a multiphase design. Phase 1 consisted in translating and structuring the questionnaire. Phase 2 aimed at assessing the validity of the content by experts. Phase 3 consisted of a pilot study (n = 150) carried out to revise the questionnaire based on the reactions of consumers representing the target group of the assessment. The questionnaire showed adequate content validity for 11 out of 14 questions (>0.79) and S-CVI/Ave > 0.80. Cronbach’s alpha values ranged from 0.08 to 0.90. The construct with insufficient results (0.08) was changed because it failed to correlate with the rest of the questionnaire. The factor analysis permitted the identification of questions that needed improvement in terms of comprehensibility, elimination of redundancies, and repetitions. The validated questionnaire included 12 questions (71 response options); 3 sections were identified: food sustainability knowledge (4 questions-30 items); sources of proteins alternative to meat (3 questions-20 items); eating behaviors (5 questions-21 items). This study showed the importance of validation before the administration on a large scale of a questionnaire on a topic such as sustainability still lacking large support from consensus documents.